2022
DOI: 10.1007/s12325-022-02119-z
|View full text |Cite
|
Sign up to set email alerts
|

Dosing Regimens of Intravitreal Aflibercept for Diabetic Macular Edema Beyond the First Year: VIOLET, a Prospective Randomized Trial

Abstract: Introduction The purpose was to compare two flexible regimens of intravitreal aflibercept (IVT-AFL) with fixed dosing every 8 weeks, beyond the first year of treatment, in patients with diabetic macular edema (DME). VIOLET was a 100-week, randomized, Phase IIIb, non-inferiority study in patients with center-involving DME previously treated with IVT-AFL for ≥ 1 year according to the European label. Methods Patients received an initial dose of IVT-AFL at study baseline an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In our study, PDME eyes constituted 33.63% of all cases, which is in line with previous reports. Due to the lack of a consensus on the definition and optimal management of PDME [ 14 , 15 ], treatment strategies such as monthly or three loading doses, pro re nata (PRN), and treat and extend (T&E) are widely used [ 26 , 27 ]. In our research, we explored PDME based on the completion of three anti-VEGF injections, consistent with current clinical practice.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, PDME eyes constituted 33.63% of all cases, which is in line with previous reports. Due to the lack of a consensus on the definition and optimal management of PDME [ 14 , 15 ], treatment strategies such as monthly or three loading doses, pro re nata (PRN), and treat and extend (T&E) are widely used [ 26 , 27 ]. In our research, we explored PDME based on the completion of three anti-VEGF injections, consistent with current clinical practice.…”
Section: Resultsmentioning
confidence: 99%
“…In the VIOLET study, it was shown that in patients with DME, both TER and PRN regimens achieve similar functional results. However, fewer injections were administered in the TER group, making higher patient adherence more likely [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A fixed bimonthly or a pro-re-nata regimen (based on strict monitoring and retreatment criteria, as stated in the DRCR.net protocol T) is recommended [ 14 ]. Treat-and-extend therapy is also a recommended regimen with non-inferior visual and anatomical improvement in DME compared to fixed dosing regimens [ 27 , 28 ], while less visual improvement was noted when the longest treatment interval was 16 weeks [ 29 ]. Despite these efforts, DME may persist.…”
Section: Discussionmentioning
confidence: 99%